Manual for Integrated District Planning, Planning Commission Government of India - Planning Commission (Planning Commission, 2008)
Decentralised planning found expression for the first time in the First Five Year Plan (1951-56), when it was suggested that the planning process be undertaken at the state and district levels too. Under these arrangements, a District Development Council (DDC) was constituted in each district to prepare plans, based in varying degrees upon a village-level participative process. The first Administrative Reforms Commission (1967) stressed the need for meaningful planning at the district level especially focusing on local variations in development patterns. The Planning Commission issued its first guidelines for district planning in 1969 that led to several states formulating district plans. However, barring a few excellent examples, these initiatives in district planning tapered away as these local planning exercises were not linked to the annual planning process in most states. These initiatives also did not incorporate urban planning processes as part of district planning.
Manual for Integrated District Planning
Government of India